The incorporation of members to the new Church’s associative forms from diverse states of life - Bahíllo Ruiz , Teodoro (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2018)
At the present the newest Church’s associative forms —new communities, movements and church families— are distinguished by gathering people from the different states of life —lay people and clergy, consecrated persons, married, even non catholics— and embracing some commitments of a collective charism which imply the whole life. It is frequent that some members of these associative forms or even all of them make a right consecration of life embracing the evangelical counsels. But every state of life has its own demands and possibilities of joining to these groups. The level of belonging and the participation forms cannot be uniform. In the present study we focus the analysis on the difficulties and implications of the incorporation of priests, consecrated persons, married and non catholics to the life of these new associative forms. Problems from different nature can be identified and they cannot be solved with the present legislation because we are facing a new and charismatic event. Experience and open ways by the doctrine are the ground to work from in order to avoid the conflicts generated by double belongings and the defence both as the movement identity as the state of life itself. Particular statutes of each association must guarantee the differentiated exercise of rights and duties of people from the different states of life who belong to the same association.
Keywords: Church movements; evangelical counsels; belonging; statutes